The Physical Body Experiences Questionnaire Simplified for Active Aging (PBE-QAG) - Cossu, Giulia (Clin Pract Epidemiol Ment Health, 2018)
BACKGROUND: The physical activity has been indicated as an experience that can help achieve positive, self-oriented own body awareness. This awareness is an aspect that tends to get worse with age. OBJECTIVE: Our study aims to verify the internal consistency of a questionnaire on physical awareness in a sample of Italian elders; a secondary objective is to measure if there is a relationship between physical awareness and perceived level of physical activity. METHODS: Cross sectional study on a consecutive sample of elderly people was administered the “Physical Body Experiences Questionnaire simplified for active aging (PBE-QAG)”, inspired by the “Physical Body Experiences Questionnaire”, modified, simplified and adapted to be used in the elderly over 65. To elderly people the International Physical Activity Questionnaire. Cronbach’s alpha was also used to assess internal reliability of the total PBE-QAG. The factor structure was evaluated through Confirmatory Factor Analyses (CFAs). RESULTS: The Cronbach’s alpha was 0.8 for the “body-mind relationship” scale, 0.81 for the “accepting your body” scale, 0.83 for the “awareness of physical skills” scale, and 0.65 for the “awareness of physical limits” scale. Cronbach’s alpha for the total PBE-QAG was 0.89. The CFA indicated a model with the 4 factors (CFI = 0.989, TLI = 0.984, RMSEA = 0.076). People who conducted physical activity assiduously or regularly and over 10 minutes showed a better score to the PBE-QAG than those who declared a sporadic activity and for “less than 10 minute”, respectively. CONCLUSION: Our study revealed that the PBE-QAG shows an excellent total internal consistency. In the Italian sample of elderly people the questionnaire shows the model with the 4 factors described in literature.